[EDSA in transition ; Marag Valley ; The Man with a thousand faces - Lazaro, Cheche (The Probe Team, 1991)
Looks at the DOTC and the DPWH putting up the EDSA Ortigas interchange; situation in Marag Valley where CCP-NPA are removed; and a profile of comedian William Nepomuceno, known as man win a thousand faces.